Experimental Study of the Dynamic Mechanical Behavior and Degradation Mechanism of Red Sandstone in Acid Dry-Wet Cycles - Wu Sun; Bin Du; Qiangqiang Cheng (Geofluids)
In this paper, the slit Hopkinson pressure bar (SHPB) experiments were conducted to investigate the dynamic mechanical characteristics of red sandstone during acid dry-wet cycles. The appearance of the samples was evaluated using scanning electron microscopy, and the process of red sandstone degradation under acid dry-wet cycles was examined. The results reveal that, as compared to neutral solution, acid solution enhances the degree of degradation induced by dry-wet cycles in red sandstone. The dynamic compressive strength and elastic modulus of red sandstone steadily decline as the number of dry-wet cycles increases, and the lower the pH of solution, the greater the reduction. The mechanism of degradation of red sandstone during acid dry-wet cycles may be explained in two ways. First, the chemical interaction between the mineral components in the sample, such as cement and feldspar, and H+ in the acid solution has accelerated the formation of secondary pores and fractures, resulting in a decrease in the cementation capacity between mineral particles. Second, partial breakdown of the major mineral particles softens the mineral skeleton.